The study on the impact of environment to metals degradation in Malaysia / Mohd Arafat Abdul Rashid and Basharuddin Abd. Rahman - Abdul Rashid, Mohd Arafat; Abd. Rahman, Basharuddin (Faculty of Mechanical Engineering, 1998)
The main objective of this project is to study impact of Malaysian environment to metals degradation. We have gathered information on the Malaysian environment and relate them to the theory of Environmentally Assisted Cracking (EAC). From this study, we believed that a few compounds in the chemical contents of the atmosphere could contribute to metals degradation. This study discusses the chemical compositions of the atmosphere and other conditions that help them in the process of metals degradation. The results of this investigation conclude that urban area and specifically the industrial zones are the more venerable to the Environmentally Assisted Cracking that the rural area.